Evidence-Based Critical Care : A Case Study Approach - Hyzy, Robert C. (Springer International Publishing : Imprint: Springer, 2017)
This textbook approaches the study of critical care with teaching in mind. In medicine "teachable moments" usually occur in clinical context, where the engagement in a real case exemplifies principles of diagnosis or therapy. In order to replicate the teaching method, selected cases are presented within each chapter offering the reader an opportunity to process and reflect on the components of the topic within a practical scenario. While medical practice attempts to be evidence-based, common approaches to diagnosis and management incorporate not only evidence but heuristics and biases which await either validation or repudiation. Hence, each chapter is divided into two segments: the "Principles of Management" section - the common approach to the care of patients having a given condition is presented - and the "Evidence Contour" section, in which each author discusses the aspects of diagnosis and management that are the subject of ongoing debate. Evidence-Based Critical Care: A Case Study Approach bridges the gulf between the traditional encyclopedic textbook and the single-hit online repository. This approach will help critical care practitioners, fellows, residents, allied health professionals and students expand their critical care knowledge in an efficient and effective manner, while being especially important for those preparing for board examinations.
Keywords: Medicine.; Critical care medicine.; elektronické knihy; electronic books